Effect of NOS3 gene polymorphism on response to Tricyclic antidepressants in migraine attacks - Molana, Aliasghar (Iran J Neurol, 2014)
Background: Migraine is a chronic neurological disorder, characterized by recurrent moderate to severe headaches. Worldwide migraine affects nearly 15%. Studies suggest that genes involved in the production of nitric oxide (NO) may act as genetic factors for migraine. NO synthase 3 (NOS3) by expressing enzyme NOS regulates endothelial derived NO. One class of medications used as first-line treatment in migraine prophylaxis is tricyclic antidepressants (TCAs). The aim of this study was to determine effects of NOS3 gene Glu298Asp polymorphism in the production of NO and response of patients to TCAs in migraine attacks. Methods: A total of 80 migraine patients were invited to participate in the study. Patients recorded the characteristics of their migraine attacks such as frequency of attacks and intensity of headaches for the 1(st) month of the study. Then peripheral blood samples were taken from all subjects in order to determine patients’ genotype distribution, mRNA expression level of NOS3 and NO content of plasma. Patients were then instructed to use 25 mg nortriptyline at night before bed for 3 months. At the end of 3(rd) month of the treatment patients again recorded the migraine characteristics for 1 month and blood sampling was performed in order to determine the level of plasma NO. Results: The patients’ genotype distribution for TT, GT, and GG was 9, 24, and 47 subjects, respectively. Mean NO level in patients with TT genotype was less in comparison to GT and GG genotypes before and after use of TCAs (P < 0.05). Mean intensity of headaches in patients with TT genotype was lower in comparison to GT and GG genotypes before and after use of TCAs (based on verbal numerical rating scale). Mean frequency of migraine attacks after use of TCAs was significantly decreased in all genotypes of NOS3 Glu298Asp polymorphism particularly in TT genotype (P < 0.05). Conclusion: Presence of T allele of the Glu298Asp polymorphism may be a factor for TT genotype patients to produce less NO and is a favorable factor for better response to TCAs in reducing migraine attacks in comparison to GT and GG genotypes.